THE IMPACT OF FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH IN THE UNITED STATES - Bewani, Hemn Adl Wali AL .; Hasan, Nawzad Majeed (International Journal of Psychosocial Rehabilitation, 2020)
International investment is strategic step for country due to lack of capital and technology transfer and it is generally well known as Foreign Direct Investment (FDI). Many policy makers and academics contend that FDI can have important positive effects on a host country’s development effort. This research examines the impact of Foreign Direct Investment on Economic Growth in the United States by multiple linear regression model and its estimation using ordinary least squares (OLS). This research classifies all the sectors to be 10 sectors. This research uses data for the period 2000 –2017 and suggests that not all forms of foreign investment seem to be beneficial to host economies. Some sectors provide positive correlation to economic growth and some provides negative effect. Nevertheless, it is significant yet, this is because there is different characteristic between developed and developing countries. Economic growth in the U.S is mostly driven by personal consumption.